J. M. W. Turner british artists - Smiles, Sam (Tate Publishing, 2013)
"J.M.W. Turner is probably the greatest painter Britain has ever produced. Both profoundly original and astonishingly prolific, he helped transform landscape painting into an expressive art form of enormous range and power. This book reveals the extent to which Turner wanted his paintings to communicate intellectually as well as emotionally; and how intensely involved he was with the culture of his times, using landscape as a vehicle for the deepest ruminations on society, politics and the human condition. Sam Smiles discusses and illustrates the whole range of Turner's work, tracking his career from the 1790s to the 1840s, exploring the themes that motivated him, and explaining his importance to subsequent generations." -- Publisher's description